Fishes from the río alvarado drainage, upper río magdalena basin, colombia - Albornoz-Garzón, Juan G.; Conde-Saldaña, Cristhian C. [UNESP]; López-Delgado, Edwin O.; García-Melo, Jorge E.; Villa-Navarro, Francisco A. (Pensoft Publishers, 2020)
An annotated list of the freshwater fishes of the Río Alvarado drainage, Upper Río Magdalena Basin is presented. Fishes were captured from nine localities, quarterly sampled between September 2012 and July 2013. A total of 36 species belonging to 14 families, distributed in five orders were collected. The most abundant species was Trichomycterus banneaui (Eigenmann, 1912) (19.4%), followed by Creagrutus affinis Steindachner, 1880 (13%), Chaetostoma thom-soni Regan, 1904 (9.1%), Trichomycterus mogotensis Ardila-Rodríguez, 2017 (7.7%), Astroblepus homodon (Regan, 1904) (6.6%), Creagrutus dulima Albornoz-Garzón, Conde-Saldaña, García-Melo, Taphorn & Villa-Navarro, 2018 (5.9%), Poecilia sphenops Valenciennes, 1846 (5.7%) and Argopleura magdalenensis (Eigenmann, 1913) (5.6%). An identification key and a complete photographic catalog of all fish species recorded in the drainage are presented.
Keywords: Andes; Characiformes; Fish diversity; Identification key; Neotropical region; Siluriformes